Prediksi beban pendinginan menggunakan Machine Learning dan parameter data cuaca - Sholahudin; Firdaus, Nazwan Hafiz; Bhowmik, Mrinal (Politeknik Negeri Sriwijaya, Indonesia, 2025)
Cooling systems account for a substantial amount of end-use energy consumption in building sector. This system is responsible for removing the heat from the building to maintain the indoor temperature at a certain comfort level standard. Prediction of cooling load in a building is useful to design the HVAC system operation and energy management efficiently. This paper presents a method for predicting instantaneous building cooling load, relying on the inputs extracted from weather data and artificial neural networks. The data sets are generated by simulating cooling load at an educational building located in Indonesia for one year using Energy Plus software. The input parameters include dry-bulb temperature, relative humidity, wind speed, wind direction, horizontal infrared radiation rate, diffuse solar radiation rate, and direct solar radiation rate. Analysis of variance and Pearson coefficient of correlation was applied to analyze the relative contribution of individual input parameters on the cooling load. Both methods have consistently shown that the dry bulb temperature is the most influential parameters, while wind speed and wind direction have less significant effect on cooling loads. The result of this study indicates that the optimized ANN model with selected input parameters has successfully predicted the cooling load with coefficient of variation (CV) of 15.26%.